2021
DOI: 10.1007/s40572-021-00317-5
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Pregnancy and Prenatal Exposure to Endocrine-Disrupting Chemicals Commonly Used in Personal Care Products

Abstract: Purpose of Review Endocrine-disrupting chemical (EDC) exposure during pregnancy is linked to adverse maternal and child health outcomes that are racially/ethnically disparate. Personal care products (PCP) are one source of EDCs where differences in racial/ethnic patterns of use exist. We assessed the literature for racial/ethnic disparities in pregnancy and prenatal PCP chemical exposures. Recent Findings Only 3 studies explicitly examined racial/ethnic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 118 publications
4
26
0
Order By: Relevance
“…We identified demographic differences in several exposures, with Hispanic ethnicity being associated with higher concentrations of multiple pesticides, phthalates, bisphenols, and parabens, consistent with prior evidence that chemical exposures (including certain phthalates, pesticides, and phenols) are frequently higher among women of color. 63 65 Racial and ethnic differences in diet and consumer product use, due in part to structural racism, may contribute to these disparities. 66 69 Many chemicals associated with race and ethnicity were also observed to be higher among women with lower educational attainment (high school or less).…”
Section: Discussionmentioning
confidence: 99%
“…We identified demographic differences in several exposures, with Hispanic ethnicity being associated with higher concentrations of multiple pesticides, phthalates, bisphenols, and parabens, consistent with prior evidence that chemical exposures (including certain phthalates, pesticides, and phenols) are frequently higher among women of color. 63 65 Racial and ethnic differences in diet and consumer product use, due in part to structural racism, may contribute to these disparities. 66 69 Many chemicals associated with race and ethnicity were also observed to be higher among women with lower educational attainment (high school or less).…”
Section: Discussionmentioning
confidence: 99%
“…While Triclosan’s critical role has been demonstrated both in reproductive processes [ 23 , 42 , 43 ] and fertility [ 21 , 44 ], its effect on ovarian function have been scarcely investigated. In a previous study, we demonstrated that this substance disrupts the functionality of cultured cells isolated from the swine corpus luteum, the transient endocrine organ that develops after ovulation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal concentrations vary by calendar year of pregnancy, geographical location and cohort. For example, low molecular weight phthalates (monoethyl phthalate or monobutyl phthalate) are higher within the CANDLE cohort compared with TIDES (table 2); these low molecular weight phthalates are primarily found in personal care products,21 23 but also these concentrations have decreased over time and CANDLE children were born before TIDES children. Overall, concentrations are similar to those measured within the US-based National Health and Nutrition Examination Survey (NHANES)24 based on year of birth (table 2).…”
Section: Introductionmentioning
confidence: 99%